Nearly efficient likelihood ratio tests of the unit root hypothesis - Michael Jansson; Morten Ørregaard Nielsen (Queen's University, Department of Economics, 2009)
Seemingly absent from the arsenal of currently available nearly efficient testing procedures for the unit root hypothesis, i.e. tests whose local asymptotic power functions are indistinguishable from the Gaussian power envelope, is a test admitting a (quasi-)likelihood ratio interpretation. We show that the likelihood ratio unit root test derived in a Gaussian AR(1) model with standard normal innovations is nearly efficient in that model. Moreover, these desirable properties carry over to more complicated models allowing for serially correlated and/or non-Gaussian innovations.
Keywords: C22; 330; Unit Root Test; Maximum-Likelihood-Methode; Stochastischer Prozess; Theorie